EKSISTENSI PEGADAIAN SYARIAH DALAM UPAYA PENINGKATAN EKONOMI USAHA MIKRO KECIL MENENGAH (IAIN Tulungagung, 2019)
ABSTRACTThe presence of pawnshop in Indonesia as a formal financial institution that moves to channel financing in the form of lending money to people in need. Then the emergence of Sharia Pawnshop that provide services to the public when facing sudden needs that have been reluctant to use conventional pawnshop. Therefore, the presence of Sharia Pawnshop can be used as an alternative for people who want to interact in a mortgage with usuary and are legal according Sharia Pawnshop, and efforts to improve the economy of MSME through Sharia Pawnshop. This type of research is library research. In searching for data sources, media such as books, articles, journals, and informations from the internet aare used as supporters of the issues to be studied. Based on the result of the research conducted, it can be described as: first, the Arrum BPKB product at Sharia Pawnshop provides an opportunity ti improve the economy of MSME, this can be seen from the understanding and financing system of the Arrum BPKB product. Second, the importance of socializing Sharia pawnshop to MSME actors in an effort to improve the economy. Third, the exixtence of sharia pawnshop can be used as an alternative in overcoming the limited capital felt by MSME actors. And the affordability of financial credit with a relatively affordable amount, easy, and timely terms and procedures.Keywords: Sharia Pawnshop, Economy, MSME